Expression of Kl67 In ER+ PR+ HER2- & ERr- PRr- HER2- Breast Cancer Patients (Journal of Surgical Sciences, 2019)
Background: Carcinoma of the breast is one of the most common malignancies in women worldwide.Objective: The current study was conducted to evaluate the role of Ki-67 as a prognosticmarker in two definite groups of breast cancer patients (ER+ve, PR+ve, HER-ve& triple negative)in Bangladesh perspective.Methods: Sixty nine female breast cancer patients operated at the surgical oncology departmentof National Institute of Cancer Research & Hospital were selected by non-probabilitysampling method and operated specimens were sent for immunohistochemical study of theER, PR, Her2/neu receptors and Ki-67 protein analysis. Statistical analysis was conductedusing SPSS version 17 for Windows software. P-value 0.05 or less was considered as significant.Result: The mean age of the patients was 46.96 years with SD of± 13.13 years. Histopathologyreports revealed that 94.2% (65/69) were suffering from duct cell carcinoma (DCC) whilelobular varieties were found in 2 cases. Majority of the patients with ER+, PR+ and Ki-67 +vestatus were between 36-50 years of age. But for Her2/neu positive cases most of patientswere above 50 years of age. In Luminal A category cancer patients 69.7% showed positiveKi-67 expression but in case of triple negative cases this percentage was 87.5%. However, thisdifference was not statistically significant.Conclusion: Scores based upon staining of ER, PR, Her2/neu and Ki-67 collectively known asIHC4 which can be used as prognostic markers in breast cancer patients.Journal of Surgical Sciences (2016) Vol. 20 (2) :37-41